1987
DOI: 10.1177/088307388700200311
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Biofeedback in the Treatment of Symptoms Associated With Reflex Sympathetic Dystrophy

Abstract: A 12-year-old male, unresponsive to therapy for symptoms associated with reflex sympathetic dystrophy, was treated by thermal biofeedback techniques. Within the first four treatment sessions, transfer of training from digital warming to warming the affected knee area produced skin temperature elevation around the gastrocnemius and patellar areas. Attenuation of localized vasospasm and cold intolerance resulted, followed by total abolition within ten sessions. After symptom alleviation, a return to premorbid ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The findings are consistent with published case studies that suggest that biofeedback approaches, including neurofeedback, can be of help to patients with chronic pain (Barowsky, Zweig, & Moskowitz, 1987;Blanchard, 1979;50 JOURNAL OF NEUROTHERAPY Sime, 2004), and suggest that current protocols recommending that thermal biofeedback be included as a treatment option for persons with CRPS-I (cf. Bruehl & Chung, 2006) be expanded to included neurofeedback as well.…”
Section: Discussionsupporting
confidence: 88%
“…The findings are consistent with published case studies that suggest that biofeedback approaches, including neurofeedback, can be of help to patients with chronic pain (Barowsky, Zweig, & Moskowitz, 1987;Blanchard, 1979;50 JOURNAL OF NEUROTHERAPY Sime, 2004), and suggest that current protocols recommending that thermal biofeedback be included as a treatment option for persons with CRPS-I (cf. Bruehl & Chung, 2006) be expanded to included neurofeedback as well.…”
Section: Discussionsupporting
confidence: 88%
“…Case reports of successful treatment of CRPS with cognitive and behavioral strategies began to appear in the 1980 s. 41,42 There are no prospective placebo-controlled trials of cognitive and behavioral therapies in the treatment of CRPS, either in adults or children. Their use is extrapolated from case reports and prospective series for other pain states, notably headache.…”
Section: Biobehavioral and Psychological Treatmentsmentioning
confidence: 98%
“…For example, Barowsky et al. (level 4 evidence) reported on a 12‐year‐old CRPS patient in whom 10 sessions of thermal biofeedback resulted in resolution of CRPS that had been resistant to previous treatments. Alioto (level 4 evidence) reported that an adult chronic CRPS patient experienced a 75% decrease in pain intensity and improved mood subsequent to a series of psychological training sessions incorporating autogenic relaxation, breathing relaxation, and muscular and temperature biofeedback.…”
Section: Psychological Interventionsmentioning
confidence: 99%